2017
DOI: 10.1371/journal.pone.0178412
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the systemic micro- and macrovasculature in stable angina: A case-control study

Abstract: AimsThe diagnosis of stable angina involves the use of probability estimates based on clinical presentation, age, gender and cardiovascular risk factors. In view of the link between the cardiac and systemic vasculature we tested whether non-invasive measures of systemic micro- and macrovascular structure and function differentiate between individuals with flow-limiting coronary artery disease (CAD) and those with normal coronary arteries (NCA).Methods and resultsWe recruited 84 patients undergoing elective cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
1
0
0
Order By: Relevance
“…A cohort study indicated similar results with our findings in lipid profile, family history of CAD, SBP, DBP, and age in CAD patients and non-CAD patients (Neisius et al , 2017). Kim et al (2016) suggested that TAC is associated with reduced blood cardiovascular risk factors.…”
Section: Discussionsupporting
confidence: 91%
“…A cohort study indicated similar results with our findings in lipid profile, family history of CAD, SBP, DBP, and age in CAD patients and non-CAD patients (Neisius et al , 2017). Kim et al (2016) suggested that TAC is associated with reduced blood cardiovascular risk factors.…”
Section: Discussionsupporting
confidence: 91%